Disposable Menstrual Products as Law’s Objects - Goldblatt, Beth; Steele, Linda (Columbia Journal of Gender and Law, 2021)
During the past few years, scholars and activists have increasingly engaged with law as a means to challenge stigma, silence, and disadvantages associated with menstruation. Menstrual items (predominantly in the form of disposable menstrual products) are becoming increasingly prominent in this “legal turn.” There have been legislative reforms to provide access to free menstrual items, litigation and legislative reforms to remove taxes on menstrual products, legislative reforms on product safety and environmental sustainability of menstrual items, and water and sanitation hygiene (‘WASH’) policies and guidelines in the context of international development interventions that focus on access to menstrual items. As regulation of disposable menstrual products assumes greater prominence in legal doctrine, feminist legal scholars are increasingly evaluating the impacts of such laws on menstruators, including in the context of diverse experiences of menstruation and menstrual injustice. But what can disposable menstrual products themselves tell us of law? In this Essay we take an object-informed approach to law in the specific context of disposable menstrual products. What insights about law might these objects provide, and how do these insights deepen our understanding of law’s relationship to menstruation, menstruators, and the worlds in which menstruators are situated? What can we appreciate about law’s role in defining, as well as recognizing and responding to, the diversity of experiences related to menstruation? How do menstrual items nuance our understanding of agency in relation to menstrual injustice? And what do these objects tell us about the limits and challenges of using law to achieve justice in relation to the embodied experiences of people who menstruate? Part II introduces some key contributions to feminist legal thinking on materiality and objects, which informs our analysis of disposable menstrual products as law’s objects. Part III introduces some of the critical threads in scholarship on disposable menstrual products, including how they relate to diversity and materiality of experiences of menstruation. Then, we turn in Part IV to explore what disposable menstrual products tell us about law’s role in menstruation, using the recent laws introduced in Scotland as a case study.